A Comparative Analysis of Field Trip Teaching Strategies in Frank McCourt’s Teacher Man and E. R. Braithwaite’s to Sir, With Love - Winarsih, Sri; Florensy Sauhenda, Angla; Wahyuniar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the portrayal of field trip strategies in Frank McCourt’s Teacher Man (2005) and E.R. Braithwaite’s to Sir, With Love (1959) through the lens of comparative literature, which enables cross-textual analysis of pedagogical themes in different socio-cultural settings. A qualitative library research approach was employed, utilizing the method of comparative literary analysis in two stages. First, close reading and manual/digital annotation of both texts were conducted to identify recurring pedagogical themes, particularly those related to field trip planning, implementation, and impact. Thematic categories were developed inductively—focusing on (1) planning and structure of field trips, (2) student engagement and learning outcomes, and (3) socio-political challenges. To strengthen reliability, inter-rater coding was applied using the agreed framework, and a Cohen’s Kappa score of 0.82 was obtained, indicating substantial agreement. The analysis reveals two contrasting approaches: McCourt’s informal and unstructured trips, marked by minimal planning, result in limited educational outcomes, while Braithwaite’s well-organized museum visit leads to meaningful student engagement and reflection. Both texts reflect how socio-political factors—particularly racial prejudice and stereotyping—influence educational practice. Additionally, McCourt faces internal challenges related to classroom management and preparation. The findings highlight that effective field trip implementation requires not only strategic planning but also cultural sensitivity and awareness of systemic bias. These insights offer practical implications for contemporary educators seeking to design inclusive and impactful experiential learning experiences.